Fine-Tuning of Atomic Energies in Relativistic Multiconfiguration Calculations - Yanting Li; Gediminas Gaigalas; Wenxian Li; Chongyang Chen; Per Jönsson (Atoms, 2023)
Ab initio calculations sometimes do not reproduce the experimentally observed energy separations at a high enough accuracy. Fine-tuning of diagonal elements of the Hamiltonian matrix is a process which seeks to ensure that calculated energy separations of the states that mix are in agreement with experiment. The process gives more accurate measures of the mixing than can be obtained in ab initio calculations. Fine-tuning requires the Hamiltonian matrix to be diagonally dominant, which is generally not the case for calculations based on <semantics>jj</semantics>-coupled configuration state functions. We show that this problem can be circumvented by a method that transforms the Hamiltonian in <semantics>jj</semantics>-coupling to a Hamiltonian in <semantics>LSJ</semantics>-coupling for which fine-tuning applies. The fine-tuned matrix is then transformed back to a Hamiltonian in <semantics>jj</semantics>-coupling. The implementation of the method into the General Relativistic Atomic Structure Package is described and test runs to validate the program operations are reported. The new method is applied to the computation of the <semantics>2s2<mspace width="3.33333pt"></mspace>1S0−2s2p<mspace width="3.33333pt"></mspace>1,3P1</semantics> transitions in C III and to the computation of Rydberg transitions in B I, for which the <semantics>2s2p2<mspace width="3.33333pt"></mspace>2S1/2</semantics> perturber enters the <semantics>2s2ns<mspace width="3.33333pt"></mspace>2S1/2</semantics> series. Improved convergence patterns and results are found compared with ab initio calculations.